Gamabufotalin Inhibits Osteoclastgenesis and Counteracts Estrogen-Deficient Bone Loss in Mice by Suppressing RANKL-Induced NF-κB and ERK/MAPK Pathways - Sun, Kaiqiang; Zhu, Jian; Deng, Yi; Xu, Ximing; Kong, Fanqi; Sun, Xiaofei; Huan, Le; Ren, Changzhen; Sun, Jingchuan; Shi, Jiangang (Frontiers in Pharmacology, 2021)
Osteolytic bone diseases are a condition of imbalanced bone hemostasis, characterized mainly by excessive bone-resorptive activity, which could predispose these populations, such as the old and postmenopausal female, to developing high risk of skeletal fragility and fracture. The nature of bone hemostasis is the coordination between the osteoblasts (OBs) and osteoclasts (OCs). Abnormal activation of osteoclasts (OCs) could compromise the bone hemostasis, constantly followed by a series of osteolytic diseases, including postmenopausal osteoporosis, osteoarthritis, and rheumatoid arthritis. Thus, medical intervention is imperative to provide adequate care for patients. The traditional Chinese medicine (TCM) Gamabufotalin (CS-6) is a newly identified natural product from ChanSu and has been used for cancer therapy owing to its good metabolic stability and fewer adverse events. Previous study suggested that CS-6 could be a novel anti-osteoporotic agent. Nevertheless, whether CS-6 suppresses RANK(receptor activator of nuclear factor-κ B ligand )/TRAF6 (TNF receptor-associated factor 6) cascades activation in OCs, as well as the effects of CS-6 on OCs differentiation and osteolytic disease, remains elusive. Therefore, in this present study, we investigated the effect of CS-6 on osteoclastogenesis and RANKL-induced signaling pathway, and and potential therapeutic application in estrogen-deficient bone loss in vivo. The results of in vitro experiment showed that CS-6 can inhibit RANKL-induced OCs formation and bone resorption in a dose-dependent manner at both the early and late stage of osteoclastogenesis. The expression of OCs marker genes TRAP, CTSK, DC-STAMP, MMP9, and β3 integrin were evidently attenuated. In addition, CS-6 could mitigate the systemic estrogen-dependent bone loss and pro-inframammary cytokines in mice in vivo. The molecular mechanism analysis suggested that CS-6 can suppress RANKL/TRAF6-induced early activation of NF-κB and ERK/MAPK signaling pathways which consequently attenuated the induction of c-Fos and NFATc1. Taken together, this present study provided the evidence that CS-6 has the potential to be a therapeutic candidate for the treatment of osteolytic conditions mediated by elevated OCs formation and bone resorption.